Translation, validity, and reliability of the Malay version of the adolescent healthy lifestyle questionnaire - Ahmad Hashim (Tanjung Malim, 2023)
Translation, validity, and reliability of the Malay version of the adolescent healthy lifestyle questionnaire by Ahmad Hashim